Hidradenocarcinoma of the Female Breast: A Surgical Approach to a Rare Skin Tumor - Alves, Duarte Gil (2023)
Clear-cell hidradenocarcinomas are extremely uncommon sweat gland tumors with a predilection for the head and neck. In the limited number of articles reporting breast involvement, the primary focus concerns this entity's histological and immunohistochemical characteristics. Since hidradenocarcinomas of the breast have the potential to resemble a primary breast carcinoma closely, diagnosis may be challenging. Therefore, the authors report the first case of hidradenocarcinoma of the breast, which features its macroscopic morphology. In addition, to increase physicians' awareness of this rare neoplasm, the article also aims to detail its surgical approach.